Knowledge and awareness of cervical cancer and screening among Malaysian women who have never had a Pap smear: a qualitative study - Wong, L.P.; Wong, Y.L.; Low, W.Y.; Khoo, E.M.; Shuib, R. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2009)
The findings highlight the importance of emphasising accurate information about cervical cancer and the purpose of Pap smear screening when designing interventions aimed at improving cervical cancer screening for Malaysian women.